Foundry Core Mixtures with Orthophosphoric Acid and Different Aluminum-Containing Compounds - Liutyi, R. V.; Tyshkovets, M. V.; Liuta, D. V. (Physics and Chemistry of Solid State, 2020)
The scientific and practical issues of the development of core mixtures for foundry, based on phosphate binding materials, are considered. The binder presented in this article differ from those previously known by the fact that scarce prepared metal phosphate binding components and powder solidifiers are not used to produce them. As a result, all developed binders are different forms of aluminum phosphates. It is shown that to obtain them it is possible to use combinations of orthophosphoric acid with aluminum-containing materials of different chemical nature. The formation of high-strength phosphate binders in the interaction of phosphoric acid with aluminosilicates and sludge wastes of aluminum production has been established. They are rationally used for processes of thermal strengthening of cores in the temperature range of 200…300 °C. The formation of binders in the interaction of orthophosphoric acid with inorganic aluminum salts are theoretically proved and practically confirmed. The results are confirmed by thermodynamic calculations, as well as by X-ray phase analysis. The compositions of the developed core mixtures and examples of their application for obtaining high-quality castings from iron and steel are presented.